Determination of Proximate, Ultimate and Structural Properties of Elephant Grass as Biomass Material for Bio-oil Production - U. J. Efetobor; S. C. Ikpeseni; S. O. Sada (Journal of Applied Sciences and Environmental Management, 2022)
Elephant grass was analyzed for its chemical properties, proximate, ultimate and structural composition and high heating value using the American Standard for Testing and Materials. (ASTM) methods. Results of proximate analysis showed moisture and ash content, fixed carbon and volatile matter content to be 0.85%, 5.86%, 14.22% and 79.24% respectively. The composition of ultimate analyses showed carbon, hydrogen, nitrogen, oxygen and sulphur content to be 54.44%, 5.59%, 0.67%, 40.95% and 0.35% respectively. The results of structural analyses showed cellulose, hemicelluloses, lignin and high heating value to be 46.26%, 29.90%, and 24.60% and 18.52MJ/kg respectively. The results of proximate, ultimate and structural analyses and high heating value showed an indication that the elephant grass is suitable for pyrolysis process because a relatively higher bio-oil yield would be expected.